Disparities in the contraceptive use among currently married women in Muslim densely populated States of India: An evidence from the nationally representative survey. - Md Illias Kanchan Sk; Selim Jahangir; Nasim Ahamed Mondal; Abhijit Basu Biswas (Epidemiology, Biostatistics and Public Health)
Background: The rationalizations for low use of contraception and high fertility among Muslims compared to other religious group in India are highly controversial. The study was aimed to explain to what extent differences in the use of contraception exist among the religious groups and also examine its associated factors in the Muslim populated States in the country.